Flow rate dynamics of pressure-compensating drippers under clogging effect - Marinaldo F. Pinto; Bruno Molle; Dinara G. Alves; Nassim Ait-Mouheb; Antonio P. de Camargo; José A. Frizzone (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The clogging dynamics of pressure-compensating drippers is still poorly addressed, and its understanding is quite important to control clogging. The aim of this study was to evaluate the flow performance of pressure-compensating drippers under clogging effect. Eight pressure-compensating emitters, model J-SC Jain PC-PLUS with nominal flow rate of 2.2 L h-1 were evaluated. The tests were run for 8 h d-1 for 4 weeks, a total of 160 h. Every 40 h, the concentration and granulometry of suspended particles were increased, by adding 125 mg L-1 of solids, composed of sand. The flow rate of the emitters was determined using a weight measurement system. Flow rate variations of the emitters did not follow a defined pattern. Clogging seems to occur randomly and abruptly. Sometimes the flow rate exceeded the nominal value (maximum relative flow rate of 182%) and other times it was lower than the nominal value (minimum relative flow rate of 0%).